La religiosité chrétienne de l’espace public aux États-Unis : histoire d’un enjeu politique - Blandine CHELINI-PONT; Robin PRESTHUS (E-REA)
American political modernity may seem paradoxical. It is based on a constitutional and political order elaborated within the framework of an a-religious liberalism and yet, it favours the religious autonomy of its society and stages itself in a decorum and national narrative both Christian-coloured. This article traces the difficult de-Christianization of the American public sphere, which appears both slow and incomplete, showing in recent years multiple signs of resistance and tension confronting the inexorable dissociation between public sphere and Christian religiosity.